The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/0265673042000209770
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermal and tissue injury behaviour in microwave thermal therapy using a porcine kidney model

Abstract: Minimally invasive microwave thermal therapies are being developed for the treatment of small renal cell carcinomas (RCC, d<3 cm). This study assessed the thermal history and corresponding tissue injury patterns resulting from microwave treatment of the porcine renal cortex. Three groups of kidneys were evaluated: (1) in vitro treated, (2) in vivo with 2-h post-treatment perfusion (acute) and (3) in vivo with 7-day post-treatment perfusion (chronic). The kidneys were treated with an interstitial water-cooled m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 21 publications
3
87
0
3
Order By: Relevance
“…Blood perfusion is temperature and time dependent and depends on the degree of microvascular stasis. The inequality between the normalized blood perfusion and the predicted degree of microvascular stasis found in this study suggests that a first order rate model may be insufficient to model renal blood perfusion response during microwave thermal therapy (123). Schutt et al .…”
Section: Modelling Of Temperature Dependence Of Tissue Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Blood perfusion is temperature and time dependent and depends on the degree of microvascular stasis. The inequality between the normalized blood perfusion and the predicted degree of microvascular stasis found in this study suggests that a first order rate model may be insufficient to model renal blood perfusion response during microwave thermal therapy (123). Schutt et al .…”
Section: Modelling Of Temperature Dependence Of Tissue Propertiesmentioning
confidence: 84%
“…compared the effect of different microvascular perfusion algorithms on ablation zone dimensions and found that the choice of microvascular perfusion algorithm and base line tissue perfusion have significant effects on final ablation zone dimensions in computer models of thermal ablation (17, 124). It is evident that the choice of modeling the temperature dependence of the electrical as well as thermal and perfusion properties have significant effects on the electrical field and temperature distribution in computer models, respectively (17, 18, 30, 64, 123). Thus, accurate models require the consideration of temperature-dependent properties, and among tissue properties in many cases perfusion and its temperature dependence is often dominating and of primary importance (30, 79, 111, 124).…”
Section: Modelling Of Temperature Dependence Of Tissue Propertiesmentioning
confidence: 99%
“…Some examples include lethal thermal dose thresholds of CEM 43 4210 min for 100% necrosis of breast tumors, 180-240 CEM 43 for prostate [23][24][25][26], 240 CEM 43 for liver during RF ablation [27], and 240 CEM 43 threshold for general soft tissue destruction and treatment of uterine fibroids with MR guided ultrasound [28,29]. The thermal isoeffect dose concept has also been extended to describe regions of thermal fixation produced during ablation, as demonstrated for kidney [30] with temperatures of $65 C; the thermal isoeffect dose that was dependent on the time of damage assay after treatment was associated with activation energies of 61-95 kcal mole…”
mentioning
confidence: 99%
“…In another study, researchers used MR-guided RF ablation of liver tumors and observed increase of temperature ranging from 60-100 °C very near the treatment device in the tumor region during ablation 52 . In microwave treatment of porcine renal cortex experiments, a temperature rise of more than 85 °C at the tip of the antenna was observed 53 . In this study, similar temperature rises ranging from 15 °C at 15mm to ~40°C at 5mm were observed in in vivo porcine liver, during ablation with Acoustxs™ applicators in the presence of PBNB.…”
Section: Resultsmentioning
confidence: 99%